The importance of vitamin D levels in children for recovery from infections - L. S. Kalagina (LLC "Diagnostics and Vaccines", 2019)
The review of the scientific literature presents current data on vitamin D in children with infections (acute respiratory diseases, pneumonia, otitis, staphylococcal infections of the skin and nasopharynx, sepsis, and others). Studies on the adverse effects of hypovitaminosis D in children on recovery from infections are given. The positive effects of vitamin D incorporation in standard infection therapy in children have been noted.